2017
DOI: 10.3389/fnmol.2017.00107
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Homocysteine Metabolism at the Crossroad of Nutrition and Sensorineural Hearing Loss

Abstract: Hearing loss (HL) is one of the most common causes of disability, affecting 360 million people according to the World Health Organization (WHO). HL is most frequently of sensorineural origin, being caused by the irreversible loss of hair cells and/or spiral ganglion neurons. The etiology of sensorineural HL (SNHL) is multifactorial, with genetic and environmental factors such as noise, ototoxic substances and aging playing a role. The nutritional status is central in aging disability, but the interplay between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 85 publications
1
27
0
2
Order By: Relevance
“…As we hypothesized, DKB122 showed protective efficacy on sensory hair cells damaged by neomycin. These results are supported by different studies that showed efficacy of omega-3 fatty acids to attenuate hearing loss [24,31].…”
Section: Discussionsupporting
confidence: 70%
“…As we hypothesized, DKB122 showed protective efficacy on sensory hair cells damaged by neomycin. These results are supported by different studies that showed efficacy of omega-3 fatty acids to attenuate hearing loss [24,31].…”
Section: Discussionsupporting
confidence: 70%
“…The methyl group‐rich amino acid methionine is first activated to form S ‐adenosylmethionine (SAM), which serves as a methyl donor in over 115 methyl transfer reactions. The loss of the methyl group results in the residual product S ‐adenosylhomocysteine (SAH), and the hydrolysis of SAH yields Hcy (Figure ) …”
Section: Introductionmentioning
confidence: 99%
“… 14 These results are also consistent with protective effects of folate on hearing and cochlear vascularization that have been observed in animal studies. 15 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…Since lower levels of folate or vitamin B12 elevate homocysteine, a metabolite thought to impair blood flow to the cochlea, these nutrients may also affect hearing through their effects on homocysteine. 14 , 15 While most studies have focused on folate and vitamin B12 deficiency or insufficiency as potential risk factors for hearing loss, excess folate from diet or folic acid from supplements and fortified foods could lead to high levels of circulating unmetabolized folic acid that could lead to neurological problems, altered DNA methylation and hearing loss. 16 19 …”
Section: Introductionmentioning
confidence: 99%